2014
DOI: 10.1530/erc-14-0173
|View full text |Cite
|
Sign up to set email alerts
|

Telotristat etiprate, a novel serotonin synthesis inhibitor, in patients with carcinoid syndrome and diarrhea not adequately controlled by octreotide

Abstract: Serotonin produced by neuroendocrine tumors is believed to be a principal cause of the diarrhea in carcinoid syndrome. We assessed the safety and efficacy of telotristat etiprate, an oral serotonin synthesis inhibitor, in patients with diarrhea associated with carcinoid syndrome. In this prospective, randomized study, patients with evidence of carcinoid tumor and ≥4 bowel movements (BMs)/day despite stable-dose octreotide LAR depot therapy were enrolled in sequential, escalating, cohorts of 4 patients/cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 11 publications
3
103
0
2
Order By: Relevance
“…Hormonally active grade 1 and 2 tumors are usually started on SSA treatment (2,5). SSA resistant tumors may benefit from additional serotonin synthesis inhibitor, telotristat etiprate (10). Grade 3 tumors are initially treated with chemotherapy (3).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonally active grade 1 and 2 tumors are usually started on SSA treatment (2,5). SSA resistant tumors may benefit from additional serotonin synthesis inhibitor, telotristat etiprate (10). Grade 3 tumors are initially treated with chemotherapy (3).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, diazoxide, which suppresses insulin release from pancreatic beta cells, is commonly used to control hypoglycemia in unresectable symptomatic insulinoma (18), and the use of SSAs is often reserved for cases refractory to diazoxide. Telotristat etiprate, an oral inhibitor of serotonin synthesis, significantly improved symptoms of refractory carcinoid syndrome and decreased urinary 5-HIAA levels in early phase clinical trials (19,20), and the randomized, double-blind, placebo-controlled phase III TELESTAR trial in patients with refractory carcinoid syndrome demonstrated that adding telotristat etiprate to SSA significantly improved symptoms of carcinoid syndrome (21).…”
Section: Functional Syndromesmentioning
confidence: 99%
“…It is a great advancement to have the first drug approved for lung NET and to have options beyond SSA in GI NET. Further, next to Matthew Kulke's group at Dana Faber University, Boston, we first explored LX1606, an oral tryptophan hydroxylase inhibitor, in patients with refractory carcinoid syndrome (NCT00853047, NCT01104415), while on therapy with somatostatin analogs (Kulke et al 2014, Pavel et al 2015. These small phase II studies in patients with carcinoid syndrome fulfilled an unmet need in patients suffering from diarrhea related to serotonin hypersecretion.…”
Section: :11mentioning
confidence: 99%